Situation Report: Czechoslovakia, 16 February 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Jaruzelski Visits Prague / by Peter Martin Economic Results for 1988 Disappointing / by Peter Martin More than 1,000 Prominent Artists Sign an Appeal / by Vladimir Kusin A New Appeal for the Release of Dissidents and a Dialogue with Society / by Jiri Pehe Cardinal Tomasek Speaks Out against Repression by the State / by Peter Martin The Independent Peace Association and the Authorities / by Jiri Pehe The Preparation of a New Czechoslovak Constitution / by Jiri Pehe Problems in the Health Care System / by Jan Obrman